Impact of liquid metal surface on plasma-surface interaction in experiments with lithium and tin capillary porous systems. (December 2020) - Budaev, V.P.; Lyublinsky, I.E.; Fedorovich, S.D.; Dedov, A.V.; Vertkov, A.V.; Komov, A.T.; Karpov, A.V.; Martynenko, Yu.V.; Van Oost, G.; Gubkin, M.K.; Lukashevsky, M.V.; Marchenkov, A.Yu.; et al.
Highlights: The lithium and tin capillary-porous systems (CPS) tested with plasma in PLM device. Evaporated lithium and tin under plasma load were studied with spectroscopy. Sustainability of tin and lithium CPSs to high-heat steady-state plasma load observed. Abstract: The lithium and tin capillary-porous systems (CPSs) were tested with steady-state plasma in the PLM plasma device which is the divertor simulator with plasma parameters relevant to divertor and SOL plasma of tokamaks. The CPS consists of tin/lithium tile fixed between two molybdenum meshs constructed in the module faced to plasma. Steady-state plasma load of 0.1 – 1 MW/m 2 on the CPS during more than 200 min was achieved in experiments on PLM which is a modeling far scrapeoff- layer and far zone of divertor plasma of a large tokamak. The heating of the CPS was controlled remotely including biasing technique which allows to regulate evaporated metal influx to plasma. After exposure, the materials of the tin and lithium CPSs were inspected and analyzed with optic and scanning electron micriscopy. Experiments have demonstrated sustainability of the tin and lithium CPSs to the high heat steady state plasma load expected in a large scale tokamak. The effect of evaporated lithium and tin on the plasma transport/radiation was studied with spectroscopy to evaluate changes of plasma properties and plasma-surface interaction.